Protocol of a longitudinal study on the specific needs of Syrian refugee families in Switzerland - Nahema El Ghaziri; Jérémie Blaser; Joëlle Darwiche; Joan-Carles Suris; Javier Sanchis Zozaya; Régis Marion-Veyron; Dario Spini; Patrick Bodenmann (BMC, 2019)
Abstract Background The ongoing Syrian civil war has led to massive population displacements, leading to the reorganization of the asylum policies of several countries. Accordingly, like other European countries, the Swiss government has recently chosen to implement a specific resettlement program. This program is characterized by the fact that the whole nuclear family is granted a work and residence permit upon arrival, and benefits from enhanced integration services. The aim of the present project is to evaluate the effects of the Swiss resettlement program, with a special focus on mental health, while adopting a family perspective. Methods The outcomes of 15 Syrian families taking part in this program will be compared to those of 15 Syrian families that came to Switzerland through other means (i.e., following the usual asylum procedure, which is much more stressful and time consuming). Each family member above 8 years old will be invited to participate to a 3-wave longitudinal survey concerning the resettlement process: upon arrival in the collective shelters, six and 12 months later. Questionnaires will be used for the evaluation of participants' mental health, risk behaviors, general health, romantic relationship, parent-child relationship, family functioning, parentification, social support, and social identities related to group belongingness. Discussion The findings of the present project will provide longitudinal information on Syrian refugees. A comprehensive approach will be adopted by screening potential difficulties that the sample may be faced with and potential strengths that participants may rely on. Accordingly, physical and mental health, as well as the quality of family functioning, the feeling of support and of belongingness to different groups will be evaluated. We will also compare the results of families who had the chance to immigrate through the Swiss resettlement program, to the results of families that did not. This comparison will allow the elaboration of hypotheses regarding adjusted asylum policies. Furthermore, it will enhance our knowledge regarding the impact of displacement on the family system. Indeed, although the role of the family for the well-being of adults and children has been established, surprisingly few studies have adopted this focus in the asylum field.